Mutu Kue Bingka Dolu pada Berbagai Konsentrasi Substitusi Terigu dengan Tepung Sorgum: Quality of Bingka Dolu at Various Concentrations of Substitution of Wheat with sorghum flour - Dunyafanisa Nurul Aulia Ryanividya; Ahmad Alamsyah; Siska Cicilia (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2022)
Bingka dolu is a traditional snack from Bima, West Nusa Tenggara. They are much favored by the community because because of the unique taste and flavor. This study aims to determine the percentage of the use of the best sorghum flour as a substitute for flour on the quality of bingka dolu. This research method was CRD with one factor, namely the percentage of substitution of flour with sorghum flour (BD), namely BD0 (100%: 0%); BD1 (80% : 20%); BD2 (605 : 40%); BD3(40% : 60%); BD4 (20% : 80%) and BD5 (0% : 100%) with parameters such as moisture content, ash, crude fiber, taste, aroma, and texture by hedonic and scoring. The results of the study were analyzed using ANOVA and further test using HSD at the level of 5%. Wheat substitution with sorghum flour effected on the moisture content, ash, crude fiber, hedonic (color, aroma, taste, texture), and scoring (texture). The use of 20% sorghum flour as a substitute for wheat was the best treatment for making bingka dolu with the characteristics of a moisture content of 35.49%; ash 0.56%; 0.23% crude fiber and organoleptic quality received by the panelists.